Preparation method of solid solution oxygen reinforced Ti15Zr alloy with ultra-fine grain structure
Through the preparation method of ultrafine crystal structure solid-solution oxygen-strengthening Ti-15Zr alloy, the existing Ti-Zr alloy has been solved, and the alloy with high mechanical properties and biosafety is achieved, which is suitable for medical implant materials.
Patent Information
- Application Number
- CN202411904074.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The strengthening mechanism of existing Ti-Zr alloys is limited, and solid-solution oxygen strengthening will reduce the plasticity of the material, and the process of preparing solid-solution oxygen controlled Ti-Zr alloys through large plastic deformation technology is still in the development stage.
The preparation method of ultrafine crystal structure solid-solution oxygen-strengthening Ti-15Zr alloy is adopted to form an alloy with excellent mechanical properties and biological properties through steps such as material mixing, cold isostatic pressure, vacuum sintering, rolling treatment, ECAP treatment and annealing treatment.
It achieves the improvement of the mechanical properties and plasticity of Ti-Zr alloys while ensuring biosafety, meets the needs of medical implant materials, and reduces the difficulty of process, making it suitable for large-scale production.
Smart Images

Figure CN119614928A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of Ti-Zr alloys, and in particular relates to a method for preparing an ultrafine grain structure solid solution oxygen strengthened Ti15Zr alloy. Background Art
[0002] With the aging of the population and the development of medical technology, the demand for high-performance biomedical materials is growing. The research and development of ultrafine-grained titanium-based materials has important scientific significance and broad application prospects. Due to the excellent mechanical properties and biological properties of Ti-Zr alloys, the research on Ti-Zr alloys has attracted extensive attention from researchers at home and abroad. In the 1990s, literature 1 developed a binary Ti-Zr alloy with a Zr content in the range of 5~25 wt.%. The alloy has excellent mechanical strength and resistance to corrosion cracking, and has good compatibility with soft and hard tissues of the human body. It can be used in components such as screws, plates, and nails for joint prosthesis implants, dental implants, and facial prosthesis fixation implants. At present, the research on medical Ti-Zr alloys at home and abroad mainly focuses on the development and preparation of Ti-Zr alloy systems with higher mechanical properties. However, the strengthening mechanism of simple binary Ti-Zr alloys is mainly solid solution strengthening of Zr, and the degree of improving material strength is still very limited. The introduction of other metal elements increases the risk of metal particle release in medical titanium-based alloys, compared with other metal element multi-component systems. The design and development of new titanium-based materials for medical implants requires improving the mechanical properties of the materials while ensuring their biosafety.
[0003] Therefore, strengthening Ti-Zr materials to improve their mechanical properties has received extensive attention in the development of medical implant materials. It has been reported that the strength, heat resistance, and corrosion resistance of titanium alloys can be improved within a certain range through oxygen solid solution strengthening design, while retaining their good plasticity, biosafety, and compatibility. However, although solid solution atoms can effectively improve the strength of Ti-Zr alloys, they still have a certain adverse effect on the plasticity of Ti-Zr alloys. Reference 2 points out that it is concluded in the literature that with the increase of oxygen content, the yield strength and tensile strength of Ti-Zr alloys are significantly improved, but its ductility and fracture toughness will decrease significantly. This phenomenon is due to the fact that oxygen atoms occupy the interstitial positions in the titanium and zirconium lattices, forming a strong solid solution strengthening effect, while inhibiting the movement of dislocations, thereby increasing the strength but reducing the plasticity of the material. Reference 3 points out that with the increase of O content in Ti-3Zr-xO, the tensile strength, yield strength, and microhardness of the alloy specimens increase, while the plasticity decreases. When O ≥ 0.3 wt.%, the plasticity of the specimen decreases significantly. Therefore, it is necessary to regulate the oxygen content and further regulate the microstructure of the Ti-Zr alloy strengthened by solid solution oxygen atoms to coordinate its strength-plasticity and achieve a synergistic improvement in the strength and plasticity of the Ti-Zr alloy.
[0004] Another effective way to improve the comprehensive mechanical properties of medical titanium-based materials is to prepare titanium alloys with ultrafine grain structures through severe plastic deformation (Sever Plastic Deformation, SPD). Ultrafine-grained titanium alloy materials obtained through severe plastic deformation technology have superior mechanical properties while maintaining the excellent corrosion resistance and bioaffinity of titanium alloys. Therefore, they are widely used to strengthen medical titanium alloy materials. As a type of severe plastic deformation technology, the equal channel angular pressing (Equal Channel Angular Pressing, ECAP) process has many advantages such as simple equipment and process, a wide range of applicable materials, and high production efficiency. However, due to the small number of movable slip systems in titanium alloys, the machinability is poor. The process of preparing Ti-Zr alloys by ECAP is still in the development stage.
[0005] In summary, although dissolved oxygen atoms can effectively improve the strength of Ti-Zr alloys, they still have a certain adverse effect on the plasticity of Ti-Zr alloys. The process of preparing solid solution oxygen-controlled Ti-Zr alloys by large plastic deformation technology is still in the development stage. Based on the above shortcomings in the preparation technology of ultrafine-grained Ti-Zr alloys, the applicant is committed to developing a preparation method for ultrafine-grained solid solution oxygen-strengthened Ti-15Zr-(0.3~0.6)O alloys. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing an ultrafine grained solid solution oxygen strengthened Ti15Zr alloy.
[0007] To achieve the above object, the present invention adopts the following technical solution: A method for preparing an ultrafine-grained solid-solution oxygen-strengthened Ti15Zr alloy comprises the following steps: (1) Material mixing Ti-15Zr alloy powder and TiO2 powder are mixed in a certain proportion and mixed using a powder mixer to ensure the uniformity of the powder.
[0008] (2) Cold isostatic pressing The mixed powder is loaded into a flexible mold and placed in a cold isostatic press for pressurization within a certain pressure range for 20 to 40 minutes to form a high-density preform.
[0009] (3) Vacuum sintering The cold isostatically pressed preform is placed in a vacuum sintering furnace and sintered at a vacuum degree of 10 -4 Pa, sintering for a certain time under certain temperature conditions, this process ensures the density and uniform microstructure of the material.
[0010] (4) Rolling treatment The sintered material is rolled through a rolling equipment at room temperature, with a reduction rate of 10-15% and a rolling speed of 0.5-1 m / s.
[0011] (5) ECAP processing After the material is rolled, it is subjected to multiple equal channel angular extrusion processes in the ECAP die system at a certain angle and extrusion speed.
[0012] (6) Annealing The ECAP treated material was annealed in a vacuum annealing furnace, and finally a Ti-15Zr-(0.3~0.6)O alloy with an ultrafine grain structure was obtained by annealing at a certain temperature for a certain time. The purpose of annealing is to eliminate the deformed structure and restore its plasticity while retaining the fine grain structure, so as to further improve the comprehensive properties of the Ti-Zr alloy.
[0013] Furthermore, in step (1), the Ti-15Zr alloy powder and the TiO2 powder are mixed in a mass ratio of 99.6:0.4.
[0014] Furthermore, the pressure of the cold isostatic press in step (2) is set to 300 MPa.
[0015] Furthermore, in step (3), the vacuum sintering temperature is 1200°C and the sintering time is 4 h.
[0016] Furthermore, in step (5), the extrusion angle is 120° and the extrusion speed is 0.3 mm / s, and two extrusion processes are performed.
[0017] Furthermore, in step (5), equal channel angular extrusion is performed in the ECAP die system. The surface of the titanium zirconium oxide rod is firstly sheathed. In order to reduce the wear of the material on the die during the deformation process, the channel corner position adopts a concentric arc transition design and is lubricated with molybdenum disulfide lubricant, thereby avoiding stress concentration and preventing cracking.
[0018] Furthermore, in step (6), the annealing temperature is 600°C and the annealing time is 1 h.
[0019] Furthermore, the composition of the Ti-15Zr-(0.3~0.6)O alloy is as follows by mass percentage: C≤0.08%, O0.3%-0.6%, N≤0.03%, H≤0.02%, Fe≤0.30%, Zr 14%-16%, and the balance is Ti.
[0020] Compared with the prior art, the ultrafine-grained solid solution oxygen-strengthened Ti15Zr alloy prepared by the present invention has excellent mechanical properties and biological properties, is widely used in the biomedical field, and has the following beneficial effects: (1) Excellent performance: Solid solution oxygen atom strengthening and ultrafine grain structuring simultaneously improve the mechanical properties of the material. On this basis, the vacuum heat treatment process eliminates the deformed structure and restores its plasticity while retaining the fine grain structure, further improving the comprehensive performance of the Ti-Zr alloy.
[0021] (2) Safety: The ultrafine-grained solid-solution oxygen-strengthened Ti15Zr alloy prepared by this method has excellent biocompatibility and mechanical properties, meeting the safety requirements of implants during their service in the human body.
[0022] (3) Low process requirements: The surface of the titanium zirconium oxide rod is sheathed to reduce the wear of the material on the mold during the deformation process. The channel corner position adopts a concentric arc transition design and lubrication conditions to avoid stress concentration and cracking, thereby achieving room temperature ECAP deformation, which is easy and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention is a preparation process of an ultrafine grained solid solution oxygen strengthened Ti15Zr alloy; Figure 2 is the element content of the Ti-15Zr-(0.3~0.6)O alloy in the patent solution of the present invention; Figure 3 The microstructure of Ti-15Zr-(0.3~0.6)O alloy after rolling; Figure 4 is the stress-strain curve of Ti-15Zr-(0.3~0.6)O alloy after rolling; Figure 5 This is the ECAP process flow in the patent solution of the present invention; Figure 6 The microstructure of Ti-15Zr-(0.3~0.6)O alloy after ECAP deformation; Figure 7 is the stress-strain curve of Ti-15Zr-(0.3~0.6)O alloy after ECAP deformation; Figure 8 The microstructure of Ti-15Zr-(0.3~0.6)O alloy after vacuum annealing; Fig. 9 This is the stress-strain curve of Ti-15Zr-(0.3~0.6)O alloy after vacuum annealing. DETAILED DESCRIPTION
[0024] In order to make the above features and advantages of the present invention more clearly understood, the following embodiments are given for detailed description. The methods of the present invention are all conventional methods in the art unless otherwise specified.
[0025] Example 1 A preparation process of an ultrafine grained solid solution oxygen strengthened Ti15Zr alloy comprises the following steps: (1) Material mixing Ti-15Zr alloy powder and TiO2 powder were mixed in a mass ratio of 99.6:0.4, and a powder mixer was used to mix the powders to ensure the uniformity of the powders; (2) Cold isostatic pressing The mixed powder was loaded into a flexible mold and placed in a cold isostatic press for 30 min at 300 MPa to form a high-density preform. (3) Vacuum sintering The cold isostatically pressed preform is placed in a vacuum sintering furnace and sintered at a vacuum degree of 10 -4 Pa, sintered at 1200 °C for 4 h; (4) Rolling treatment The sintered material was rolled through a rolling equipment at room temperature, with a set reduction rate of 15% and a rolling speed of 1 m / s; (5) ECAP processing After the material is rolled, it is subjected to two passes of equal channel angular extrusion in the ECAP die system at an extrusion angle of 120° and an extrusion speed of 0.3 mm / s; (6) Annealing The ECAP treated material was annealed in a vacuum annealing furnace at 600 °C for 1 h to obtain a Ti-15Zr-(0.3~0.6)O alloy with an ultrafine grain structure, whose composition by mass percentage is: C 0.03%, O 0.38%, N 0.01%, H 0.01%, Fe 0.15%, Zr 14.9%, and the balance is Ti. Figure 2 shown.
[0026] The existing Ti-Zr alloy is not strong enough, and solid solution oxygen strengthening will have an adverse effect on plasticity. The process of preparing ultrafine grain Ti-Zr alloy by ECAP is still in the development stage. The present invention improves the mechanical properties of the material by solid solution oxygen atom strengthening and ultrafine grain structuring. On this basis, the vacuum heat treatment process is used to eliminate the deformed structure and restore its plasticity while retaining the fine grain structure, further improving the comprehensive performance of the Ti-Zr alloy to meet the safety of the Ti-Zr alloy in the process of human service.
[0027] like Figure 1 As shown, the patent scheme of the present invention proposes a preparation process of an ultrafine-grained solid solution oxygen-strengthened Ti15Zr alloy: first, Ti-15Zr alloy powder and TiO2 powder are mixed in a certain proportion, the oxygen content of the Ti-Zr-O material is designed to be 0.30-0.60 wt.%, a powder mixer is used to mix the powder to ensure uniform mixing of the powders, and then the mixed powder is loaded into a flexible mold, placed in a cold isostatic press for pressurization within a certain pressure range for 20-40 minutes to form a high-density preform; then the preform after cold isostatic pressing is placed in a vacuum sintering furnace and sintered at a vacuum degree of 10 -4 Pa, sintering at a certain temperature for different times, this process ensures the density and uniform microstructure of the material; the sintered material is rolled by a rolling equipment at room temperature, the reduction rate is set to 10~15%, and the rolling speed is 0.5~1m / s; then multiple equal channel angular extrusion treatments are carried out under certain angles and extrusion speeds, and finally, a Ti-15Zr-(0.3~0.6)O alloy with an ultrafine grain structure is obtained by annealing at a certain temperature for different times.
[0028] The patented solution of the present invention adopts the method of cold isostatic pressing + vacuum sintering to directly obtain Ti-15Zr-(0.3~0.6)O material. Figure 2As shown, in a preferred embodiment of the patent scheme of the present invention, Ti-15Zr alloy powder and TiO2 powder are mixed in a mass ratio of 99.6:0.4, and then the mixed powder is loaded into a flexible mold and placed in a cold isostatic press for pressurization. The pressure is set to 300 MPa for 30 min. Then, the preform after cold isostatic pressing is placed in a vacuum sintering furnace and sintered at a vacuum degree of 10 -4 The samples were sintered at 1200 °C for 4 h.
[0029] The patent scheme of the present invention rolls the sintered material through a rolling device at room temperature to further improve the density and uniformity of the microstructure of the material. In a preferred embodiment of the patent scheme of the present invention, the reduction rate is set to 15%, the rolling speed is 1 m / s, and the microstructure of the material is as follows Figure 3 The stress-strain curve is as follows: Figure 4 shown.
[0030] like Figure 5 As shown, the rolled material in the patent scheme of the present invention is subjected to equal channel angular extrusion in the ECAP die system. The surface of the titanium zirconium oxide rod is firstly sheathed. In order to reduce the wear of the material on the die during the deformation process, the channel corner position adopts a concentric arc transition design and passes the lubrication condition to avoid stress concentration and prevent cracking. In a preferred embodiment of the patent scheme of the present invention, two-pass materials with an extrusion angle of 120° and an extrusion speed of 0.3mm / s are selected. The microstructure is as follows Figure 6 The stress-strain curve is as follows: Figure 7 shown.
[0031] In the patent scheme of the present invention, the material after ECAP treatment is annealed in a vacuum annealing furnace. In a preferred embodiment of the patent scheme of the present invention, the material after 2 passes of ECAP deformation is selected, the annealing temperature is set to 600 ° C, the time is 1h, and the microstructure is as follows Figure 8 The stress-strain curve is as follows: Fig. 9 As shown in Figure 3, the purpose of annealing treatment is to eliminate the residual stress introduced during the ECAP process and retain the ultrafine grain structure to further improve the comprehensive properties of the Ti-Zr alloy.
[0032] Figure 3 The metallographic microstructure of the invention preparation process up to the step (4) of rolling treatment, wherein the average grain size is 2 μm (the grains are relatively fine); Figure 4 The stress-strain curve of the invention preparation process to the step (4) rolling treatment, wherein the tensile strength is 917 MPa, the yield strength is 859 MPa; the elongation is 9.39%; Figure 5(5) The process of ECAP treatment, the first picture is the copper-clad Ti-15Zr-(0.3~0.6)O, the second picture is the material placed in the mold, the third picture is extruded by the press, and the fourth picture is the end of extrusion; Figure 6 The metallographic microstructure of the inventive preparation process up to (5) ECAP treatment step, wherein the grain size is 760 nm (ultrafine grain structure ≤ 1 μm); Figure 7 The stress-strain curve of the invention preparation process to the step (5) ECAP treatment, wherein the tensile strength is 1080 MPa, the yield strength is 932 MPa; the elongation is 8.59%; Figure 8 The metallographic microstructure of the invention preparation process up to step (6) annealing treatment, wherein the grain size is 880nm (ultrafine grain structure ≤1μm); Fig. 9 This is the stress-strain curve of the invention preparation process up to the step (6) annealing treatment, in which the tensile strength is 996 MPa, the yield strength is 945 MPa, the elongation is 13.1%, and the highest strength-ductility product (strength*elongation).
[0033] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
[0034] [1] Steinemann S. Binary titanium-zirconium alloy for surgical implants and a suitable manufacturing process: US Patent 8, 168, 012[P].2012-5-1. [2] Fukuo M, Kariya S, Umeda J, et al.Strengthening mechanisms ofpowder metallurgy extruded CP titanium materials with zirconium and oxygensolid solution via decomposition of ZrO2 additives insintering[J]. MaterialsTransactions, 2019, 60(9): 1881-1889. [3] Fei Yang, Wang Tao, Miao Runjie, et al. Effect of trace oxygen content on microstructure and mechanical properties of Ti-3Zr alloy[J]. Rare Metals and Cemented Carbides, 2019, 6.
Claims
1. A method for preparing an ultrafine grained solid solution oxygen strengthened Ti15Zr alloy, characterized in that: The following steps are involved: (1) Material mixing Mix Ti-15Zr alloy powder and TiO2 powder in a certain proportion and use a powder mixer to mix the powder to ensure the uniformity of the powder; (2) Cold isostatic pressing The mixed powder is loaded into a flexible mold and placed in a cold isostatic press for pressurization within a certain pressure range to form a high-density preform; (3) Vacuum sintering The cold isostatically pressed preform is placed in a vacuum sintering furnace and sintered at a vacuum degree of 10 -4 Pa, sintering for a period of time under certain temperature conditions; (4) Rolling treatment The sintered material is rolled through a rolling device at room temperature, with a set reduction rate of 10-15% and a rolling speed of 0.5-1 m / s; (5) ECAP processing After the material is rolled, it is subjected to multiple equal channel angular extrusion processes at a certain angle and extrusion speed in the ECAP die system; (6) Annealing The ECAP treated material was annealed in a vacuum annealing furnace at a certain temperature for a certain time to obtain a Ti-15Zr-(0.3~0.6)O alloy with an ultrafine grain structure.
2. The method according to claim 1, characterized in that In step (1), the Ti-15Zr alloy powder and the TiO2 powder are mixed in a mass ratio of 99.6:0.
4.
3. The method according to claim 1, characterized in that In step (2), the pressure of the cold isostatic press is set to 300 MPa.
4. The method according to claim 1, characterized in that: The pressure treatment time in step (2) is 20 to 40 minutes.
5. The method according to claim 1, characterized in that In step (3), the vacuum sintering temperature is 1200°C and the sintering time is 4 h.
6. The method according to claim 1, characterized in that In step (5), the extrusion angle is 120° and the extrusion speed is 0.3 mm / s.
7. The method according to claim 1, characterized in that In step (5), two extrusion processes are performed.
8. The method according to claim 1, characterized in that The annealing temperature in step (6) is 600°C.
9. The method according to claim 1, characterized in that: The annealing time in step (6) is 1 h.
10. The method according to claim 1, characterized in that The composition of the Ti-15Zr-(0.3~0.6)O alloy is as follows by mass percentage: C≤0.08%, O 0.3%-0.6%, N≤0.03%, H≤0.02%, Fe≤0.30%, Zr 14%-16%, and the balance is Ti.
Citation Information
Patent Citations
Binary titanium-zirconium alloy for surgical implants and a suitable manufacturing process
US8168012B2
Titanium oxide-titanium carbide whisker toughened magnesium alloy biomedical material
CN106119742A
Method for preparing Ti-Zr-O alloy through powder metallurgy
CN117210711A
Aluminum-carbon metal matrix composites for fasteners
CN119301817A
Process for equal channel angular pressing fine grain titanium round tube
US10960448B1